Kajian Literatur: Aplikasi Metode Ekstraksi Modern Untuk Mengekstraksi Senyawa Fenolik dari Bahan Alam - Firdiyansyah, Moh. Rofiqi; Sindu Sakti, Aditya; Wulan Kusumo, Djati; Saiful Amin, Muhammad (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2024)
Phenolic compounds are phytochemicals obtained from plants as a response to stress. This compound has benefits as an antioxidant. Moreover, these compounds have an important role in preventing and treating several disorders such as atherosclerosis, brain dysfunction, diabetes mellitus, and cancer. Obtaining phenolic compounds from natural products, required an extraction method. A modern extraction method is an extraction process using several high technological instruments, to obtain high-yield extract in a short time. This review article performed to summarizes several modern extraction methods that can applied to extract phenolic compounds from natural products. The process of preparing this article was carried out comprehensively using various databases such as Google Scholar, Pubmed, Science Direct, Portal Garuda, NCBI, and BMC, using the keywords